LlWRKY39 is involved in thermotolerance by activating LlMBF1c and interacting with LlCaM3 in lily (Lilium longiflorum). (4th February 2021) - Ding, Liping; Wu, Ze; Teng, Renda; Xu, Sujuan; Cao, Xing; Yuan, Guozhen; Zhang, Dehua; Teng, Nianjun
Abstract: WRKY transcription factors (TFs) are of great importance in plant responses to different abiotic stresses. However, research on their roles in the regulation of thermotolerance remains limited. Here, we investigated the function of LlWRKY39 in the thermotolerance of lily ( Lilium longiflorum 'white heaven'). According to multiple alignment analyses, LlWRKY39 is in the WRKY IId subclass and contains a potential calmodulin (CaM)-binding domain. Further analysis has shown that LlCaM3 interacts with LlWRKY39 by binding to its CaM-binding domain, and this interaction depends on Ca 2+ . LlWRKY39 was induced by heat stress (HS), and the LlWRKY39-GFP fusion protein was detected in the nucleus. The thermotolerance of lily and Arabidopsis was increased with the ectopic overexpression of LlWRKY39 . The expression of heat-related genes AtHSFA1, AtHSFA2, AtMBF1c, AtGolS1, AtDREB2A, AtWRKY39, and AtHSP101 was significantly elevated in transgenic Arabidopsis lines, which might have promoted an increase in thermotolerance. Then, the promoter of LlMBF1c was isolated from lily, and LlWRKY39 was found to bind to the conserved W-box element in its promoter to activate its activity, suggesting that LlWRKY39 is an upstream regulator of LlMBF1c . In addition, a dual-luciferase reporter assay showed that via protein interaction, LlCaM3 negatively affected LlWRKY39 in the transcriptional activation of LlMBF1c, which might be an important feedback regulation pathway to balance the LlWRKY39-mediated heat stress response (HSR). Collectively, these results imply that LlWRKY39 might participate in the HSR as an important regulator through Ca 2+ -CaM and multiprotein bridging factor pathways.